Multiple signal transduction mechanisms leading to the secretion of 5- hydroxytryptamine by MTC cells, a neurectodermally derived cell line - Tamir, H (J Neurosci, 1990)
Parafollicular (PF) cells of the thyroid gland are neural crest derivatives. These cells remain plastic even in adult animals and can be induced to exhibit neural properties when exposed to NGF in vitro. A human cell line derived from PF cells, medullary thyroid carcinoma (MTC), has previously been shown to synthesize and store 5-HT, a serotonin-binding protein (SBP), and several neuropeptides; moreover, when grown in impoverished media, MTC cells display neural properties. The purpose of the current study was to utilize MTC cells as a neurally relevant model system to investigate factors involved in mediating 5-HT secretion. Electron microscopic immunocytochemistry revealed that secretory vesicles of MTC cells costore immunoreactive 5-HT with SBP and calcitonin. The cAMP derivative, N6-2′-O-dibutyryl-adenosine 3′,5′- cyclic monophosphate (dibutyryl-cAMP; 1.0 mM) increased the concentration of 5-HT in MTC cells and almost doubled the rate of synthesis of 5-HT from L-tryptophan. Dibutyryl-cAMP also significantly increased the secretion of 5-HT. Cycloheximide (20 micrograms/ml) and anisomycin (20 microM) inhibited the dibutyryl-cAMP-induced increase of 5-HT release, suggesting that this action of dibutyryl-cAMP requires protein synthesis. Cholera toxin (1.0 microgram/ml) and forskolin (0.05 mM) in the presence of the phosphodiesterase inhibitor 3-isobutyl-1- methylxanthine (1.0 mM) both increased 5-HT biosynthesis and secretion. Attempts were made to identify a ligand that stimulates cAMP-mediated secretion of 5-HT. Both thyroid-stimulating hormone (TSH: 50 mU/ml) and elevated [Ca2+]e (7.0 mM), each of which acts as a secretogogue for PF cells, stimulated the secretion of 5-HT. The effect of TSH was Ca2(+)- dependent. Immunocytochemistry with monoclonal antibodies to the TSH receptor confirmed that these receptors are present on MTC cells. Neither TSH nor elevated [Ca2+]e elevated cAMP levels. Measurements of Fura-2 fluorescence, however, indicated that both TSH and elevated [Ca2+]e increased cytosolic calcium ([Ca2+]i), as did elevation of [K+]e. It is concluded that exocytosis can be triggered in MTC cells by multiple signal transduction mechanisms. Either cAMP or elevated [Ca2+]i can stimulate secretion; however, a secretogogue that increases cAMP has yet to be identified.